Assessing Teacher Competences and Their Impact on Inclusive Education for Children with Developmental Difficulties in Kosovo - Kaltrina Osmani; Natasha Stanojkovska-Trajkovska (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji)
In Kosovo, the inclusion of special education needs (SEN) in regular classrooms is growing, yet teachers often lack the necessary preparation. Effective management requires competency, inclusive training and development. This study explored the relationship between teacher competences, inclusive education training, and professional support in managing classrooms with children with SEN in Kosovo. We employed a mixed-methods approach, distributing structured questionnaires to 57 elementary and secondary school teachers and conducting a literature review. Descriptive statistics revealed that 98.20% of children receiving special education services had impairments, indicating a robust commitment to addressing SEN. The emphasis was on early intervention, as evidenced by the creation of 96.50% Individualized Education Plans (IEPs) in the first grade and the active analysis of previous program data by 87.70% of teachers. A chi-square test found a significant correlation between training in inclusive education and teachers' proficiency in managing inclusive classrooms (p-value < 0.01). However, 8.80% of teachers reported limited data access, highlighting the need for further training and support. IEP goals often prioritized social skills (12.10%) and adaptive behavior (11.8%), emphasizing the necessity of thorough educator preparation. The study underscores the critical role of inclusive education training in enhancing teacher competency. Although most SEN children receive necessary services, challenges like restricted data access require solutions through continuous professional development. Hypothesis testing showed professional support significantly boosts teacher confidence in inclusive practices (p-value < 0.05), emphasizing continuous training.